Duration biased distribution of clinical and immunological phenotypes in active SLE - Yan, Qingran; Liu, Bei; Yang, Minjie; Li, Qianqian; Wang, Jieying; Li, Ting; Lu, Liangjing (Frontiers in Immunology, 2022)
Abstract Objective: This study is aimed to map the clinical and immunological features of active lupus patients with different disease duration. Methods: For clinical phenotype analysis, we enriched eligible medical records with active SLE (SLEDAI-2k≥8) from the Renji Lupus registry, a single-center database of hospitalized SLE patients with standard care, which covered national-wide patients. Patients with repeated hospitalization records in this enrichment were analyzed longitudinally as validation for the cross-sectional study above. Results: We enriched a total of 1313 eligible records on active SLE (SLEDAI-2k≥8) for cross-sectional analysis. Stratified into four groups by a 5-year interval of disease duration, these active SLE patients showed a significantly shifting clinical phenotype along with the duration (ascending nephritis, pulmonary hypertension and descending fever, cutaneous symptoms, arthritis, and neuropsychiatric manifestations), especially in stratifications with disease onset age ≤ 45 years old. A longitudinal analysis of 55 patients with repeated hospitalizations for active lupus showed a similar trend. In the cross-sectional study of 222 records with full information on serology and lymphocyte subsets, peripheral B cell proportion, anti-dsDNA antibody, and serum IgG/IgM negatively correlated with duration, while CD8+ T cell proportion was positively correlated (P values, 0.029-4.8×10-17), which were supported by the sensitivity analysis in patient subgroups according to disease onset age and recent treatment. Multivariate linear regression identified duration as the only significant associator with both B cell and CD8+ T cell proportion (P values, 8.9×10-8 and 7.6×10-5, respectively). These duration biased immune phenotypes were highly consistent with the longitudinal observation in 14 patients with repeated hospitalizations. Conclusions: Both clinical and immunological features of active SLE are significantly duration biased distributed, which merits further investigations in the evolution of SLE pathogenesis.